2009
DOI: 10.1111/j.1742-4658.2008.06852.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphates from Mycobacterium bovis– potent inhibitors of class III adenylate cyclases

Abstract: cAMP generation in bacteria is often stimulated by sudden, but lasting, changes in extracellular conditions, whereas intracellular cAMP concentrations quickly settle at new levels. As bacteria lack G‐proteins, it is unknown how bacterial adenylate cyclase (AC) activities are modulated. Mycobacterium tuberculosis has 15 class III AC genes; therefore, we examined whether mycobacteria contain a factor that may regulate AC activities. We identified mycobacterial polyphosphates with a mean chain length of 72 residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…While, the trigger(s) of sudden changes in expression of ACs and subsequent cellular cAMP levels at late growth stages of Mtb is yet to identify, the intracellular polyphosphates may be an important determinant of cellular cAMP levels [42]. Polyphosphates, generated by the activity of an enzyme known as polyphosphate kinase, is highly accumulated at the stationary phase as well as under different stress conditions in Mtb [43], and are known to inhibit the activity of ACs [42]. These information warrant further studies to analyze the effect of polyphosphates on intracellular cAMP levels.…”
Section: Discussionmentioning
confidence: 99%
“…While, the trigger(s) of sudden changes in expression of ACs and subsequent cellular cAMP levels at late growth stages of Mtb is yet to identify, the intracellular polyphosphates may be an important determinant of cellular cAMP levels [42]. Polyphosphates, generated by the activity of an enzyme known as polyphosphate kinase, is highly accumulated at the stationary phase as well as under different stress conditions in Mtb [43], and are known to inhibit the activity of ACs [42]. These information warrant further studies to analyze the effect of polyphosphates on intracellular cAMP levels.…”
Section: Discussionmentioning
confidence: 99%
“…adenylyl cyclases and E. coli formate hydrogen lyase transcriptional activator. Bacterial peptidoglycan and muramyl dipeptides activate AC from Candida albicans (Xu et al ., ) and polyphosphates are potent inhibitors of different ACs from Mycobacterium tuberculosis but do not affect the AC from E. coli (Guo et al ., ).…”
Section: Adenylyl Cyclasesmentioning
confidence: 97%
“…Recent reports have shown that altered miRNA levels are also associated with the phenotypical changes of HSC during the myofibroblastic transition process including the induction of ECM proteins (Guo et al, 2009a; Ji et al, 2009) (Table 1). …”
Section: Dysregulation Of Mirna In Liver Fibrosismentioning
confidence: 99%